2014
DOI: 10.5155/eurjchem.5.1.133-137.923
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted synthesis of 2-amino-6-methoxy-4H-benzo[h]chromene derivatives

Abstract: A convenient and efficient method using microwave assisted synthesis of 4H-benzo[h]chromenes (7 and 8), by the reaction of 4-methoxy-1-naphthol (1) with a mixture of aromatic aldehydes (2) and malononitrile (3) or ethyl cyanoacetate (5) and also, by the reaction of 4-methoxy-1-naphthol (1) with α-cyanocinnamonitriles (4) or ethyl α-cyanocinnamates (6) in ethanolic piperidine solution was examined. Structures of the newly synthesized compounds were established on the basis of spectral data, IR, 1 H NMR, 13 C NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…In continuation of the previous works [15,25,26,27,28,29,30,31,34,35,36,37], it seemed interesting to synthesize some new 7 H -benzo[ h ]chromeno[2,3- d ]-pyrimidine and 14 H -benzo-14 H -benzo[ h ]chromeno[3,2- e ][1,2,4]-triazolo[1,5- c ]pyrimidine derivatives and to appraise their antimicrobial activities. The structure-activity relationships (SAR) are discussed in this work to correlate between the substituent effects and the activities that aid in drug design.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In continuation of the previous works [15,25,26,27,28,29,30,31,34,35,36,37], it seemed interesting to synthesize some new 7 H -benzo[ h ]chromeno[2,3- d ]-pyrimidine and 14 H -benzo-14 H -benzo[ h ]chromeno[3,2- e ][1,2,4]-triazolo[1,5- c ]pyrimidine derivatives and to appraise their antimicrobial activities. The structure-activity relationships (SAR) are discussed in this work to correlate between the substituent effects and the activities that aid in drug design.…”
Section: Introductionmentioning
confidence: 53%
“…2-Amino-4-(4-fluoro/chloro/bromophenyl)-6-methoxy-4 H -benzo[h]chromene-3-carbonitriles 4a – c , 2-ethoxymethyleneamino-4-(4-fluoro/chloro/bromophenyl)-6-methoxy-4 H -benzo[ h ]chromene-3-carbonitriles 5a – c and 9-amino-7-(4-fluoro/chloro/bromophenyl)-5-methoxy-8-imino-7 H -benzo[ h ]-chromeno[2,3- d ]pyrimidines 6a – c were prepared by reported methods ([34,35,36,37], [29,30,31] and [29,30,31], respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Chromenes have been renowned for their incredible biological functions, which assisted their assimilation into various applications such as antimicrobial activities [10][11][12][13][14], hypolipidemic [15], antileishmanial, antiviral, anti-HIV, antianaphylactic activities [16][17][18], insecticidal [19], targeting of c-Src kinase enzyme [20,21], anticancer and cytotoxic activities [22][23][24][25], cell cycle analysis, apoptotic effects, caspase 3/7, and inhibition of the topoisomerase enzyme [26][27][28][29][30][31][32][33]. Among the synthetic strategies to acquire chromene molecules, microwave irradiation is one of the most efficacious and eco-friendly procedures, which facilitates the isolation of the desired compounds in a short period of time and results in good yields [34][35][36][37]. Furthermore, the dihydrofolate reductase (DHFR) enzyme used as a therapeutic target in the treatment of infections through NADPH is used in the reduction of DHFR and is involved in the synthesis of cell proliferation raw material [38].…”
Section: Introductionmentioning
confidence: 99%
“…Mccarroll and co-workers also reported that tephrosin, a viable anti-lung carcinoma drug, as well as Acronycine, a drug targeting colon, lung, and ovary tumors, obstruct the cell proliferation through their binding to the β-tubulin specific site, which subsequently induces apoptosis through microtubule polymerization [ 11 ]. Furthermore, chromene molecules are deemed ‘privileged medicinal scaffolds’ due to their unique pharmacological and biological activities [ 5 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%